Stress-Driven Transposable Element De-repression Dynamics and Virulence Evolution in a Fungal Pathogen. (23rd September 2019) - Fouché, Simone; Badet, Thomas; Oggenfuss, Ursula; Plissonneau, Clémence; Francisco, Carolina Sardinha; Croll, Daniel
Abstract: Transposable elements (TEs) are drivers of genome evolution and affect the expression landscape of the host genome. Stress is a major factor inducing TE activity; however, the regulatory mechanisms underlying de-repression are poorly understood. Plant pathogens are excellent models to dissect the impact of stress on TEs. The process of plant infection induces stress for the pathogen, and virulence factors (i.e., effectors) located in TE-rich regions become expressed. To dissect TE de-repression dynamics and contributions to virulence, we analyzed the TE expression landscape of four strains of the major wheat pathogen Zymoseptoria tritici . We experimentally exposed strains to nutrient starvation and host infection stress. Contrary to expectations, we show that the two distinct conditions induce the expression of different sets of TEs. In particular, the most highly expressed TEs, including miniature inverted-repeat transposable element and long terminal repeat- Gypsy element, show highly distinct de-repression across stress conditions. Both the genomic context of TEs and the genetic background stress (i.e., different strains harboring the same TEs) were major predictors of de-repression under stress. Gene expression profiles under stress varied significantly depending on the proximity to the closest TEs and genomic defenses against TEs were largely ineffective to prevent de-repression. Next, we analyzed the locus encoding the Avr3D1 effector. We show that the insertion and subsequent silencing of TEs in close proximity likely contributed to reduced expression and virulence on a specific wheat cultivar. The complexity of TE responsiveness to stress across genetic backgrounds and genomic locations demonstrates substantial intraspecific genetic variation to control TEs with consequences for virulence.